Pengaruh Kualitas Produk dan Harga terhadap Minat Beli pada Yamaha All New Nmax (Studi pada Konsumen Yamaha Flagship Shop Kota Semarang) - Awal Sukma Primajati; Sari Listyorini; Ari Pradhanawati (Universitas Diponegoro, 2022)
Yamaha All New NMAX is one of the products from Yamaha that is most in demand by the public. The decision of consumers to have the intention to buy products offered by companies is one of the important factors in competition between companies. The problem arose when the Yamaha All New NMAX, which is one of the pioneers of large automatic motorcycles in Indonesia, had to be less competitive with its competitors. The disadvantage of this motorcycle is that the design offered is less elegant and luxurious. In addition, there are still some consumer complaints about the quality of the Yamaha All New NMAX such as the standard version in terms of security, the competitor has been equipped with a smart key or keyless feature. Yamaha sees pricing as the most important thing and should get special attention. If consumers are already willing to the price offered, then the product will be accepted by the wider community. So looking at the problems above this study aims to determine the effect of product quality and price on the interest in buying Yamaha All New NMAX. As for the type of research used, namely explanatory research, the number of samples in this study was 94 respondents who had purchased Yamaha All New NMAX at Yamaha Flagship Shop Semarang for the last 4 years using a non-probabilty sampling technique. This research technique uses purposive sampling. In this study, data processing using the SPSS application, the results showed , results were obtained that product quality has a positive and significant influence on buying interest, price has a positive and significant influence on buying interest, product quality and price have a positive and significant influence on buying interest. Based on the results of the research that has been done, the researcher has several suggestions, namely, improving product quality to be even better, providing better price offers to be accepted by consumers, providing product innovation and correcting product deficiencies in order to increase consumer satisfaction and increase customer satisfaction. consumer purchases.Yamaha All New NMAX merupakan salah produk dari Yamaha yang paling banyak diminati oleh masyarakat. Keputusan konsumen untuk memiliki niat membeli produk yang ditawarkan oleh perusahaan merupakan salah satu faktor penting dalam persaingan antar perusahaan. Permasalahan muncul ketika Yamaha All New NMAX yang merupakan salah satu pelopor motor matic besar yang ada di Indonesia harus kalah saing dengan kompetitornya. Kekurangan yang dimiliki oleh sepeda motor ini yaitu desain yang ditawarkan kurang elegan dan mewah. Selain itu, masih terdapat beberapa keluhan konsumen mengenai kualitas dari yamaha All New NMAX seperti versi standar dari sisi keamanan, sang kompetitornya sudah dibekali fitur smart key atau keyless. Yamaha melihat penetapan harga sebagai hal yang paling penting dan harus mendapatkan perhatian khusus. Jika konsumen sudah bersedia dengan harga yang ditawarkan, maka produk tersebut akan diterima oleh masyarakat luas. Maka melihat permasalahan diatas penelitian ini bertujuan untuk mengetahui pengaruh kualitas produk dan harga terhadap minat beli Yamaha All New NMAX. Adapun tipe penelitian yang digunakan yaitu explanatory research, jumlah sampel pada penelitian ini yaitu sebanyak 94 responden yang pernah melakukan pembelian Yamaha All New NMAX di Yamaha Flagship Shop Semarang selama 4 tahun terakhir dengan menggunakan teknik non-probabilty sampling yaitu purposive sampling. Penelitian ini, data diproses menggunakan Aplikasi SPSS, didapatkan hasil, bahwa kualitas produk memiliki pengaruh positif dan signifikan terhadap minat beli, harga memiliki pengaruh positif dan signifikan terhadap minat beli, kualitas produk dan harga memiliki pengaruh positif dan signifikan terhadap minat beli.